2022
DOI: 10.1136/bmjopen-2021-058561
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric manifestations and associated risk factors among hospitalised patients with COVID-19 in Edo State, Nigeria: a cross-sectional study

Abstract: ObjectiveTo estimate the prevalence of depression and anxiety and identify associated risk factors in hospitalised persons with confirmed COVID-19 in Edo, Nigeria.DesignA multicentre cross-sectional survey.SettingPatients with COVID-19 hospitalised at the three government-designated treatment and isolation centres in Edo State, Nigeria.ParticipantsThe study was conducted from 15 April to 11 November 2020 among 489 patients with confirmed COVID-19 and in treatment and isolation centres in Edo State, Nigeria. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…Depressed mood was the only symptom that was associated with elevated SARS-CoV-2 anti-spike antibody titers in this study. The mechanism by which depressed mood occurs after COVID-19 recovery is not clearly understood, although it has been reported that longer periods of isolation due to COVID-19 might be associated with an increased risk of having depression and anxiety (22). Antibody titers are considered to reflect the level of the immune response to COVID-19, and higher levels are more likely to be found in patients with a strong immune response and prolonged period of isolation in the hospital, which may explain the increased risk of developing a depressed mood.…”
Section: Discussionmentioning
confidence: 99%
“…Depressed mood was the only symptom that was associated with elevated SARS-CoV-2 anti-spike antibody titers in this study. The mechanism by which depressed mood occurs after COVID-19 recovery is not clearly understood, although it has been reported that longer periods of isolation due to COVID-19 might be associated with an increased risk of having depression and anxiety (22). Antibody titers are considered to reflect the level of the immune response to COVID-19, and higher levels are more likely to be found in patients with a strong immune response and prolonged period of isolation in the hospital, which may explain the increased risk of developing a depressed mood.…”
Section: Discussionmentioning
confidence: 99%
“…The psychological state of college students was found to be more vulnerable to the outbreak of COVID-19 than other groups [100]. Additionally, the existing literature on the mental health consequences of the pandemic on both the general population and persons with confirmed COVID-19 showed that depression, anxiety, and other mental health problems are common [101]. Moreover, the pandemic has been associated with increased health-related socioeconomic vulnerability among women, which is prevalent and associated with alarmingly high rates of mental health problems [102].…”
Section: Psychological and Social Consequences Of Long Covidmentioning
confidence: 98%